Teorija kompleksnosti spada v več tokov teorije sistemov - Mulej, Matjaž (Organizacija (Kranj), 2006)
Complexity is not only a mathematical discipline, but it tackles all features that are complex (= entangled / intricate due to relations between their components). Some references about systems theory call such features systems, while others put systems equal to mental pictures of features tackling complex features, mainly, again. One may conclude that complexity theory renews principles of the General Systems Theory, after the latter have lost their battle competing against narrow specialization. This battle gave birth to five main streams of systems theory and cybernetics. Complexity theory, as a mathematical discipline, would belong to stream 1. As a science dealing with complex features in an interdisciplinary way, it would belong in stream 3, if using a mathematical basis, or in stream 5, if using a philosophical one.
Keywords: sistemi; teorija sistemov; kibernetika; kompleksnost